Preparation method of half-cell solid oxide anode

Preparation of semi-battery solid oxide anode through static-stacking tablets-Wen and other static pressure processes, solve the problem of unevenness and cracking of flat fuel batteries when firing large-sized single batteries, improved the flatness and mechanical strength of the anode It is suitable for solid oxide fuel cells.

CN119340407AInactive Publication Date: 2025-01-21XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411874895.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When firing large-sized single cells, flat-panel solid oxide fuel cells are prone to problems of unevenness and cracking, resulting in a decrease in mechanical strength and hindering the large-scale application of fuel cells.

Method used

Adopt a static pressure process such as flow-stacked sheet-warming, prepare anode film bands, transition layer tapes, and electrolyte layer belts in turn, and compound and sintering through thermal pressure stacked tablets to increase the leveling of semi-battery solid oxide anode and Mechanical strength.

Benefits of technology

Through this method, the flatness and mechanical strength of the semi -battery solid oxide anode, solve the problem of incompleteness and reduced mechanical strength caused by inconsistency caused by inconsistencies in existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340407A_ABST
    Figure CN119340407A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a half-cell solid oxide anode. The method comprises the following steps: 1, preparing anode slurry and preparing an anode film belt through a tape casting method; 2, preparing transition layer slurry and preparing a transition layer film belt through a tape casting method; 3, preparing electrolyte layer slurry and preparing an electrolyte layer membrane belt by a tape casting method; 4, cutting the anode film belt, the transition layer film belt and the electrolyte layer film, and performing hot-pressing lamination; 5, performing warm isostatic pressing molding; and 6, sintering to obtain the half-cell solid oxide anode. The casting-lamination-temperature isostatic pressing technology is adopted, the anode film belt, the transition layer film belt and the electrolyte layer film belt are prepared in sequence, hot-pressing lamination compounding and sintering are conducted, the flatness and mechanical strength of the half-cell solid oxide anode are improved, the technology is simple and economical, and the method is suitable for the field of cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fuel cells, and in particular to a method for preparing a half-cell solid oxide anode. Background Art

[0002] Solid oxide fuel cell (SOFC) is a new type of power generation device that can efficiently convert the chemical energy in fuel gas (such as hydrogen, natural gas, coal gas, etc.) into electrical energy and thermal energy without precious metal catalysts. It adopts an all-solid-state structure, low emissions and low noise. It is an ideal decentralized power station and centralized power station technology, and can also be used in vehicle auxiliary power supply, portable power supply, etc. Due to its advantages of high energy conversion efficiency, low environmental pollution, and strong fuel adaptability, SOFC is highly expected in today's global energy shortage, relatively single energy supply form and increasingly serious environmental pollution.

[0003] SOFC usually adopts two types of structures: tubular and flat. The two battery structures have different characteristics, and therefore have different application ranges. The advantages of flat-type SOFC are simple preparation process and low cost; and the flat-type SOFC has uniform current collection and short flow path, so the output power density of the flat-type battery is also higher than that of the tubular type. In addition, the single cell must not only meet the requirements of electrical and electrochemical properties, but also have high requirements for the flatness and mechanical strength of the single cell in practical applications. However, when the flat-type SOFC is fired with large-size (10cm×10cm) single cells, the sample is always uneven or even cracked after sintering. The insufficient flatness of the single cell will bring great difficulties to the assembly of the battery into a stack, and the cracking of the single cell will greatly reduce the sintering molding rate, hindering the large-scale application of fuel cells.

[0004] Some scholars have proposed a press-firing method. Although this method improves the flatness of the single cell to a certain extent, it also sacrifices some of the mechanical strength of the single cell. Moreover, the press-firing plate used in the press-firing process has high requirements for parameters such as porosity and flatness, so this method also increases the preparation cost of the single cell. Therefore, how to simply and economically prepare single cells with high flatness and high mechanical strength is a problem that must be solved before the large-scale application of solid oxide fuel cells. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a half-cell solid oxide anode in view of the shortcomings of the above-mentioned prior art. The method adopts a tape casting-lamination-warm isostatic pressing process to sequentially prepare an anode film strip, a transition layer film strip and an electrolyte layer film strip, and hot press lamination and sintering, thereby improving the flatness and mechanical strength of the half-cell solid oxide anode, and solving the problems of insufficient flatness of the cell due to inconsistent shrinkage between layers and reduced mechanical strength due to press firing in the existing half-cell firing process.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a half-cell solid oxide anode, characterized in that the method comprises the following steps: Step 1, preparing an anode film strip: at room temperature, nickel oxide powder, corn starch, triethanolamine, 3YSZ, ethanol, polyethylene glycol PEG, polyvinyl butyral PVB, and dioctyl phthalate DOP are sequentially added into a ball mill for ball milling to form a stable and uniform anode slurry, and then the anode slurry is filtered and degassed, and then a tape casting method is used to prepare an anode film strip with uniform thickness; Step 2, preparing a transition layer membrane tape: at room temperature, nickel oxide powder, triethanolamine, 8YSZ, ethanol, polyethylene glycol PEG, polyvinyl butyral PVB, and dioctyl phthalate DOP are added to a ball mill for ball milling to form a stable and uniform transition layer slurry, and then the transition layer slurry is filtered and degassed, and then a transition layer membrane tape with uniform thickness is prepared by a casting method; Step 3, preparing an electrolyte layer membrane tape: at room temperature, adding 8YSZ, triethanolamine, ethanol, polyethylene glycol PEG, polyvinyl butyral PVB, and dioctyl phthalate DOP into a ball mill for ball milling to form a stable and uniform electrolyte layer slurry, and then filtering and degassing the electrolyte layer slurry, and then using a casting method to prepare an electrolyte layer membrane tape with uniform thickness; Step 4: pre-pressing the anode green body: respectively cutting the anode membrane strip prepared in step 1, the transition layer membrane strip prepared in step 2, and the electrolyte layer membrane strip prepared in step 3 into the same size, then hot-pressing and laminating the cut anode membrane strips to form an anode support layer, and then hot-pressing and laminating the cut transition layer membrane strips and electrolyte layer membrane strips to form a transition layer and an electrolyte layer on the anode support layer in sequence, to obtain a pre-pressed body; Step 5, pressing and molding the anode green body: evacuate the pre-pressed body obtained in step 5 and put it into a warm isostatic press for pressing and molding to obtain the anode green body; Step 6: Sintering: Place the anode green body obtained in step 5 into a high-temperature sintering and binder removal furnace for sintering to obtain a half-cell solid oxide anode.

[0007] The above-mentioned method for preparing a half-cell solid oxide anode is characterized in that, in step 1, 10 to 15 parts of nickel oxide powder, 1 to 2 parts of corn starch, 1 to 2 parts of triethanolamine, 10 to 15 parts of 3YSZ, 10 to 15 parts of ethanol, 1 to 2 parts of polyethylene glycol PEG, 1 to 2 parts of polyvinyl butyral PVB, and 1 to 2 parts of dioctyl phthalate DOP are taken by mass; In step one, the ball milling speed is 200r / min~400r / min, and the ball milling time is 2h~5h; the degassing time is 10min~60min, and the process of the tape casting method is: the degassed anode slurry is tape-casted and spread and dried at 40℃~80℃ for 1h~5h, and the thickness of the anode film strip is 80μm~150μm.

[0008] The above-mentioned method for preparing a half-cell solid oxide anode is characterized in that, in step 2, 5 to 10 parts of nickel oxide powder, 0.5 to 1 part of triethanolamine, 5 to 10 parts of 8YSZ, 8 to 12 parts of ethanol, 0.5 to 1 part of polyethylene glycol PEG, 1 to 2 parts of polyvinyl butyral PVB, and 0.5 to 1 part of dioctyl phthalate DOP are taken by mass; In step 2, the ball milling speed is 200r / min~400r / min, the ball milling time is 2h~5h, the degassing time is 10min~60min, and the process of the casting method is: the degassed transition layer slurry is spread out by casting and dried at 40℃~80℃ for 1h~5h, and the thickness of the transition layer membrane tape is 10μm~30μm.

[0009] The above-mentioned method for preparing a half-cell solid oxide anode is characterized in that, in step 3, 8 to 10 parts of 8YSZ, 0.1 to 1 part of triethanolamine, 5 to 8 parts of ethanol, 0.1 to 1 part of polyethylene glycol PEG, 0.1 to 1 part of polyvinyl butyral PVB, and 0.1 to 0.5 part of dioctyl phthalate DOP are taken by weight; In step three, the ball milling speed is 200r / min~400r / min, the ball milling time is 2h~5h, the degassing time is 10min~60min, and the process of the casting method is: the degassed electrolyte layer slurry is spread out by casting and dried at 40℃~80℃ for 1h~5h, and the thickness of the electrolyte layer membrane tape is 10μm~30μm.

[0010] The above-mentioned method for preparing a half-cell solid oxide anode is characterized in that the heating temperature of the upper and lower plates of the hot-pressed lamination in step four is 30°C~50°C, the lamination pressure is 10MPa~35MPa, the holding time is 3min~15min, the thickness of the anode support layer is 350μm~500μm, and the thickness of the pre-pressed body is 370μm~590μm.

[0011] The above-mentioned method for preparing a half-cell solid oxide anode is characterized in that the heating temperature of the pressing molding in step five is 30°C~50°C, the pressure is 10MPa~35MPa, and the holding time is 3min~15min.

[0012] The above-mentioned method for preparing a half-cell solid oxide anode is characterized in that the sintering process described in step 6 is: heating from room temperature to 600°C~800°C at a rate of 0.5°C / min~2°C / min and keeping the temperature for 4h~12h, and then continuing to heat to 1200°C~1400°C at a rate of 0.5°C / min~2°C / min and keeping the temperature for 4h~12h. In the sintering process, the binder is fully removed at low temperature, and sintering is performed at a high temperature stage.

[0013] Compared with the prior art, the present invention has the following advantages: 1. The present invention first adopts a tape casting method to prepare an anode membrane strip, a transition layer membrane strip and an electrolyte layer membrane strip, and then compounds them by hot pressing lamination, and performs warm isostatic pressing to form and sinter them to obtain a half-cell solid oxide anode, so that each membrane strip is pressed more evenly, thereby improving the flatness and mechanical strength of the half-cell solid oxide anode, and solving the problems of insufficient battery flatness due to inconsistent shrinkage between layers and reduced mechanical strength due to press firing in the existing half-cell firing process.

[0014] 2. The half-cell solid oxide anode prepared by the present invention has higher flatness and mechanical strength, and the preparation process is simple, economical and efficient, and is suitable for the field of solid oxide fuel cells (SOFC).

[0015] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a cross-sectional microstructure diagram of the half-cell solid oxide anode prepared in Example 3 of the present invention.

[0017] Figure 2 This is a power density performance diagram of a full cell assembled from the half-cell solid oxide anode prepared in Example 3 of the present invention.

[0018] Figure 3 This is a physical picture of the battery cell after sintering the half-cell solid oxide anode green body prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0019] Example 1 This embodiment includes the following steps: Step 1, preparing an anode film strip: at room temperature, take 10 parts of nickel oxide powder, 1 part of corn starch, 1 part of triethanolamine, 10 parts of 3YSZ, 10 parts of ethanol, 1 part of polyethylene glycol PEG, 1 part of polyvinyl butyral PVB, and 1 part of dioctyl phthalate DOP, and add them into a ball mill in sequence for ball milling at a speed of 200 r / min for 2 hours to form a stable and uniform anode slurry, and then filter and degas the anode slurry for 10 minutes, and then use a tape casting method to tape-cast the degassed anode slurry and dry it at 40°C for 1 hour to prepare an anode film strip with a thickness of 80 μm and uniform thickness; Step 2, prepare a transition layer membrane tape: at room temperature, take 5 parts of nickel oxide powder, 0.5 parts of triethanolamine, 5 parts of 8YSZ, 8 parts of ethanol, 0.5 parts of polyethylene glycol PEG, 1 part of polyvinyl butyral PVB, and 0.5 parts of dioctyl phthalate DOP, add them into a ball mill for ball milling at a speed of 200 r / min for 2 hours to form a stable and uniform transition layer slurry, and then filter and deaerate the transition layer slurry for 10 minutes, and then use a casting method to cast the deaerated transition layer slurry and dry it at 61°C for 3 hours to prepare a transition layer membrane tape with a thickness of 30 μm and uniform thickness; Step 3, prepare the electrolyte layer membrane tape: at room temperature, take 8 parts of 8YSZ, 0.5 parts of triethanolamine, 6 parts of ethanol, 0.2 parts of polyethylene glycol PEG, 0.6 parts of polyvinyl butyral PVB, and 0.15 parts of dioctyl phthalate DOP, add them into a ball mill for ball milling at a speed of 300r / min for 3 hours to form a stable and uniform electrolyte layer slurry, and then filter and deaerate the electrolyte layer slurry for 30 minutes, and then use a casting method to cast the deaerated electrolyte layer slurry and dry it at 50°C for 2 hours to prepare an electrolyte layer membrane tape with a thickness of 20μm and uniform thickness; Step 4, pre-pressing the anode green body: the anode membrane strip prepared in step 1, the transition layer membrane strip prepared in step 2, and the electrolyte layer membrane strip prepared in step 3 are cut into the same size respectively, and then the cut anode membrane strips are laminated by hot pressing to form an anode support layer with a thickness of 350 μm, and then the cut transition layer membrane strips and electrolyte layer membrane strips are laminated by hot pressing to form a transition layer and an electrolyte layer on the anode support layer in sequence, to obtain a pre-pressed body with a thickness of 390 μm; the upper and lower plates of the hot pressing laminate are heated to 50°C, the lamination pressure is 20 MPa, and the holding time is 8 min; Step 5, pressing and molding the anode green body: evacuate the pre-pressed body obtained in step 5 and put it into a warm isostatic press for pressing and molding to obtain the anode green body; the heating temperature of the pressing and molding is 50° C., the pressure is 20 MPa, and the holding time is 5 min; Step six, sintering: the anode green body obtained in step five is placed in a high-temperature sintering and debinding furnace for sintering to obtain a half-cell solid oxide anode; the sintering process is: heating from room temperature to 600°C at a rate of 0.5°C / min and keeping warm for 4 hours, and then continuing to heat to 1200°C at a rate of 1°C / min and keeping warm for 8 hours.

[0020] Example 2 This embodiment includes the following steps: Step 1, preparing an anode film strip: at room temperature, take 15 parts of nickel oxide powder, 2 parts of corn starch, 2 parts of triethanolamine, 15 parts of 3YSZ, 15 parts of ethanol, 2 parts of polyethylene glycol PEG, 2 parts of polyvinyl butyral PVB, and 2 parts of dioctyl phthalate DOP, and add them into a ball mill in sequence for ball milling at a speed of 400r / min for 5 hours to form a stable and uniform anode slurry, and then filter and degas the anode slurry for 60 minutes, and then use a tape casting method to tape-cast the degassed anode slurry and dry it at 80°C for 5 hours to prepare an anode film strip with a thickness of 150μm and uniform thickness; Step 2, prepare a transition layer membrane tape: at room temperature, take 10 parts of nickel oxide powder, 1 part of triethanolamine, 10 parts of 8YSZ, 12 parts of ethanol, 1 part of polyethylene glycol PEG, 2 parts of polyvinyl butyral PVB, and 1 part of dioctyl phthalate DOP, add them into a ball mill for ball milling at a speed of 400r / min for 5 hours to form a stable and uniform transition layer slurry, and then filter and deaerate the transition layer slurry for 60 minutes, and then use a casting method to cast the deaerated transition layer slurry and dry it at 80°C for 5 hours to prepare a transition layer membrane tape with a thickness of 30μm and uniform thickness; Step 3, prepare the electrolyte layer membrane tape: at room temperature, take 10 parts of 8YSZ, 1 part of triethanolamine, 8 parts of ethanol, 0.8 parts of polyethylene glycol PEG, 1 part of polyvinyl butyral PVB, and 0.5 parts of dioctyl phthalate DOP and add them into a ball mill for ball milling at a speed of 400r / min for 5h to form a stable and uniform electrolyte layer slurry, and then filter and deaerate the electrolyte layer slurry for 60min, and then use a casting method to cast the deaerated electrolyte layer slurry and dry it at 80°C for 4h to prepare an electrolyte layer membrane tape with a thickness of 30μm and uniform thickness; Step 4, pre-pressing the anode green body: the anode membrane strip prepared in step 1, the transition layer membrane strip prepared in step 2, and the electrolyte layer membrane strip prepared in step 3 are cut into the same size respectively, and then the cut anode membrane strips are laminated by hot pressing to form an anode support layer with a thickness of 500 μm, and then the cut transition layer membrane strips and electrolyte layer membrane strips are laminated by hot pressing to form a transition layer and an electrolyte layer on the anode support layer in sequence, to obtain a pre-pressed body with a thickness of 590 μm; the upper and lower plates of the hot pressing laminate are heated to 50°C, the lamination pressure is 35 MPa, and the holding time is 15 min; Step 5, pressing and molding the anode green body: evacuate the pre-pressed body obtained in step 5 and put it into a warm isostatic press for pressing and molding to obtain the anode green body; the heating temperature of the pressing and molding is 50° C., the pressure is 35 MPa, and the holding time is 15 min; Step six, sintering: the anode green body obtained in step five is placed in a high-temperature sintering and debinding furnace for sintering to obtain a half-cell solid oxide anode; the sintering process is: heating from room temperature to 700°C at a rate of 2°C / min and keeping warm for 12h, then continuing to heat to 1400°C at a rate of 2°C / min and keeping warm for 4h.

[0021] Example 3 This embodiment includes the following steps: Step 1, preparing an anode film strip: at room temperature, take 12 parts of nickel oxide powder, 2 parts of corn starch, 2 parts of triethanolamine, 12 parts of 3YSZ, 15 parts of ethanol, 1.5 parts of polyethylene glycol PEG, 1.5 parts of polyvinyl butyral PVB, and 1 part of dioctyl phthalate DOP, and add them into a ball mill in sequence for ball milling at a speed of 300 r / min for 4 hours to form a stable and uniform anode slurry, and then filter and degas the anode slurry for 40 minutes, and then use a tape casting method to tape-cast the degassed anode slurry and dry it at 50°C for 2 hours to prepare an anode film strip with a thickness of 100 μm and uniform thickness; Step 2, prepare a transition layer membrane tape: at room temperature, take 7 parts of nickel oxide powder, 0.8 parts of triethanolamine, 7 parts of 8YSZ, 10 parts of ethanol, 0.5 parts of polyethylene glycol PEG, 1.2 parts of polyvinyl butyral PVB, and 1 part of dioctyl phthalate DOP, add them into a ball mill for ball milling at a speed of 350 r / min for 4 hours to form a stable and uniform transition layer slurry, and then filter and deaerate the transition layer slurry for 60 minutes, and then use a casting method to cast the deaerated transition layer slurry and dry it at 50°C for 2 hours to prepare a transition layer membrane tape with a thickness of 25 μm and uniform thickness; Step 3, prepare the electrolyte layer membrane tape: at room temperature, take 8YSZ 9 parts, triethanolamine 0.5 parts, ethanol 8 parts, polyethylene glycol PEG 1 part, polyvinyl butyral PVB 0.8 parts, dioctyl phthalate DOP 0.25 parts and add them into a ball mill for ball milling at a speed of 400r / min for 3h to form a stable and uniform electrolyte layer slurry, and then filter and degas the electrolyte layer slurry for 20min, and then use the casting method to cast the degassed electrolyte layer slurry and dry it at 60°C for 2h to prepare an electrolyte layer membrane tape with a thickness of 25μm and uniform thickness; Step 4, pre-pressing the anode green body: the anode membrane strip prepared in step 1, the transition layer membrane strip prepared in step 2, and the electrolyte layer membrane strip prepared in step 3 are cut into the same size respectively, and then the cut anode membrane strips are laminated by hot pressing to form an anode support layer with a thickness of 420 μm, and then the cut transition layer membrane strips and electrolyte layer membrane strips are laminated by hot pressing to form a transition layer and an electrolyte layer on the anode support layer in sequence, to obtain a pre-pressed body with a thickness of 450 μm; the upper and lower plates of the hot pressing laminate are heated to 40°C, the lamination pressure is 25 MPa, and the holding time is 5 min; Step 5, pressing and molding the anode green body: evacuate the pre-pressed body obtained in step 5 and put it into a warm isostatic press for pressing and molding to obtain the anode green body; the heating temperature of the pressing and molding is 35° C., the pressure is 30 MPa, and the holding time is 10 min; Step six, sintering: the anode green body obtained in step five is placed in a high-temperature sintering and debinding furnace for sintering to obtain a half-cell solid oxide anode; the sintering process is: heating from room temperature to 800°C at a rate of 0.5°C / min and keeping the temperature for 6 hours, and then continuing to heat to 1350°C at a rate of 1°C / min and keeping the temperature for 8 hours.

[0022] Figure 1 This is a cross-sectional view of the half-cell solid oxide anode prepared in this embodiment. Figure 3 It can be seen that the structure of the half-cell solid oxide anode from top to bottom is an electrolyte layer, a transition layer and an anode support layer.

[0023] Figure 2 This is a power density performance diagram of a full cell assembled from a half-cell solid oxide anode prepared in this embodiment. The diameter of the full cell is Φ25 mm. Figure 2 It can be seen that the power density of the full battery is 1W / cm 2 , with good electrochemical performance.

[0024] Figure 3 This is a photo of the cell after sintering the half-cell solid oxide anode green body prepared in this example. Figure 3It can be seen that the battery cell is flat and has no cracks, and the sintering effect is good.

[0025] Example 4 This embodiment includes the following steps: Step 1, preparing an anode film strip: at room temperature, 14 parts of nickel oxide powder, 1 part of corn starch, 1.5 parts of triethanolamine, 10 parts of 3YSZ, 14 parts of ethanol, 1 part of polyethylene glycol PEG, 1 part of polyvinyl butyral PVB, and 1.5 parts of dioctyl phthalate DOP are added to a ball mill in sequence for ball milling at a speed of 250 r / min for 3 hours to form a stable and uniform anode slurry, and then the anode slurry is filtered and degassed for 40 minutes, and then the degassed anode slurry is cast and spread by a casting method and dried at 70°C for 2 hours to prepare an anode film strip with a thickness of 120 μm and uniform thickness; Step 2, prepare a transition layer membrane tape: at room temperature, take 9 parts of nickel oxide powder, 0.75 parts of triethanolamine, 9 parts of 8YSZ, 11 parts of ethanol, 0.75 parts of polyethylene glycol PEG, 1.25 parts of polyvinyl butyral PVB, and 0.5 parts of dioctyl phthalate DOP, add them into a ball mill for ball milling, the ball milling speed is 350r / min, and the ball milling time is 3.5h to form a stable and uniform transition layer slurry, and then filter and deaerate the transition layer slurry, the deaeration time is 40min, and then use the casting method to cast the deaerated transition layer slurry and dry it at 60°C for 4h to prepare a transition layer membrane tape with a thickness of 25μm and uniform thickness; Step 3, prepare the electrolyte layer membrane tape: at room temperature, take 10 parts of 8YSZ, 0.75 parts of triethanolamine, 7 parts of ethanol, 0.25 parts of polyethylene glycol PEG, 0.5 parts of polyvinyl butyral PVB, and 0.3 parts of dioctyl phthalate DOP and add them into a ball mill for ball milling at a speed of 400r / min for 5 hours to form a stable and uniform electrolyte layer slurry, and then filter and deaerate the electrolyte layer slurry for 60 minutes, and then use a casting method to cast the deaerated electrolyte layer slurry and dry it at 45°C for 3 hours to prepare an electrolyte layer membrane tape with a thickness of 30μm and uniform thickness; Step 4, pre-pressing the anode green body: the anode membrane strip prepared in step 1, the transition layer membrane strip prepared in step 2, and the electrolyte layer membrane strip prepared in step 3 are cut into the same size respectively, and then the cut anode membrane strips are laminated by hot pressing to form an anode support layer with a thickness of 400 μm, and then the cut transition layer membrane strips and electrolyte layer membrane strips are laminated by hot pressing to form a transition layer and an electrolyte layer on the anode support layer in sequence, to obtain a pre-pressed body with a thickness of 350 μm; the upper and lower plates of the hot pressing laminate are heated to 40°C, the lamination pressure is 25 MPa, and the holding time is 10 min; Step 5, pressing and molding the anode green body: evacuate the pre-pressed body obtained in step 5 and put it into a warm isostatic press for pressing and molding to obtain the anode green body; the heating temperature of the pressing and molding is 30° C., the pressure is 25 MPa, and the holding time is 10 min; Step six, sintering: the anode green body obtained in step five is placed in a high-temperature sintering and debinding furnace for sintering to obtain a half-cell solid oxide anode; the sintering process is: heating from room temperature to 600°C at a rate of 0.5°C / min for 8 hours, and then continuing to heat to 1370°C at a rate of 1°C / min for 12 hours.

[0026] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a half-cell solid oxide anode, characterized in that: The method comprises the following steps: Step 1, preparing an anode film strip: at room temperature, nickel oxide powder, corn starch, triethanolamine, 3YSZ, ethanol, polyethylene glycol PEG, polyvinyl butyral PVB, and dioctyl phthalate DOP are sequentially added into a ball mill for ball milling to form a stable and uniform anode slurry, and then the anode slurry is filtered and degassed, and then a tape casting method is used to prepare an anode film strip with uniform thickness; Step 2, preparing a transition layer membrane tape: at room temperature, nickel oxide powder, triethanolamine, 8YSZ, ethanol, polyethylene glycol PEG, polyvinyl butyral PVB, and dioctyl phthalate DOP are added to a ball mill for ball milling to form a stable and uniform transition layer slurry, and then the transition layer slurry is filtered and degassed, and then a transition layer membrane tape with uniform thickness is prepared by a casting method; Step 3, preparing an electrolyte layer membrane tape: at room temperature, adding 8YSZ, triethanolamine, ethanol, polyethylene glycol PEG, polyvinyl butyral PVB, and dioctyl phthalate DOP into a ball mill for ball milling to form a stable and uniform electrolyte layer slurry, and then filtering and degassing the electrolyte layer slurry, and then using a casting method to prepare an electrolyte layer membrane tape with uniform thickness; Step 4: pre-pressing the anode green body: respectively cutting the anode membrane strip prepared in step 1, the transition layer membrane strip prepared in step 2, and the electrolyte layer membrane strip prepared in step 3 into the same size, then hot-pressing and laminating the cut anode membrane strips to form an anode support layer, and then hot-pressing and laminating the cut transition layer membrane strips and electrolyte layer membrane strips to form a transition layer and an electrolyte layer on the anode support layer in sequence, to obtain a pre-pressed body; Step 5, pressing and molding the anode green body: evacuate the pre-pressed body obtained in step 5 and put it into a warm isostatic press for pressing and molding to obtain the anode green body; Step 6: Sintering: Place the anode green body obtained in step 5 into a high-temperature sintering and binder removal furnace for sintering to obtain a half-cell solid oxide anode.

2. The method for preparing a half-cell solid oxide anode according to claim 1, characterized in that: In step 1, 10-15 parts of nickel oxide powder, 1-2 parts of corn starch, 1-2 parts of triethanolamine, 10-15 parts of 3YSZ, 10-15 parts of ethanol, 1-2 parts of polyethylene glycol PEG, 1-2 parts of polyvinyl butyral PVB, and 1-2 parts of dioctyl phthalate DOP are taken by mass; In step one, the ball milling speed is 200r / min~400r / min, and the ball milling time is 2h~5h; the degassing time is 10min~60min, and the process of the tape casting method is: the degassed anode slurry is tape-casted and spread and dried at 40℃~80℃ for 1h~5h, and the thickness of the anode film strip is 80μm~150μm.

3. The method for preparing a half-cell solid oxide anode according to claim 1, characterized in that: In step 2, 5 to 10 parts of nickel oxide powder, 0.5 to 1 part of triethanolamine, 5 to 10 parts of 8YSZ, 8 to 12 parts of ethanol, 0.5 to 1 part of polyethylene glycol PEG, 1 to 2 parts of polyvinyl butyral PVB, and 0.5 to 1 part of dioctyl phthalate DOP are taken by weight; In step 2, the ball milling speed is 200r / min~400r / min, the ball milling time is 2h~5h, the degassing time is 10min~60min, and the process of the casting method is: the degassed transition layer slurry is spread out by casting and dried at 40℃~80℃ for 1h~5h, and the thickness of the transition layer membrane tape is 10μm~30μm.

4. The method for preparing a half-cell solid oxide anode according to claim 1, characterized in that: In step 3, 8-10 parts of 8YSZ, 0.1-1 parts of triethanolamine, 5-8 parts of ethanol, 0.1-1 parts of polyethylene glycol PEG, 0.1-1 parts of polyvinyl butyral PVB, and 0.1-0.5 parts of dioctyl phthalate DOP are taken by weight; In step three, the ball milling speed is 200r / min~400r / min, the ball milling time is 2h~5h, the degassing time is 10min~60min, and the process of the casting method is: the degassed electrolyte layer slurry is spread out by casting and dried at 40℃~80℃ for 1h~5h, and the thickness of the electrolyte layer membrane tape is 10μm~30μm.

5. The method for preparing a half-cell solid oxide anode according to claim 1, characterized in that: In step 4, the heating temperature of the upper and lower plates of the hot-pressed lamination is 30°C~50°C, the lamination pressure is 10MPa~35MPa, the holding time is 3min~15min, the thickness of the anode support layer is 350μm~500μm, and the thickness of the pre-pressed body is 370μm~590μm.

6. The method for preparing a half-cell solid oxide anode according to claim 1, characterized in that: The heating temperature of the pressing molding in step 5 is 30° C. to 50° C., the pressure is 10 MPa to 35 MPa, and the holding time is 3 min to 15 min.

7. The method for preparing a half-cell solid oxide anode according to claim 1, characterized in that: The sintering process in step six is: heating from room temperature to 600°C~800°C at a rate of 0.5°C / min~2°C / min and keeping warm for 4h~12h, then continuing to heat to 1200°C~1400°C at a rate of 0.5°C / min~2°C / min and keeping warm for 4h~12h.

Citation Information

Patent Citations

  • Single cell as well as preparation method and application thereof

    CN103613105A

  • Preparation method of cathode current collector of solid oxide fuel cell

    CN104064786A

  • Preparation method of metal-supported solid oxide fuel cell, and fuel cell

    CN113258112A

  • Tubular solid oxide fuel cell manufacturing method based on tape casting and lamination technology

    CN116666713A

  • Preparation method of fuel cell and fuel cell

    CN118782849A